Russia gives International Space Station a lift. - Zak, A.
Lobbyists in Moscow convinced the Russian Duma (parliament) to provide a shot in the arm to the country's manned space program. In a last-minute move to preserve its nation's role in the worlds largest space venture, the Duma unanimously approved a US 50 million dollars increase in funding for the cash-strapped industry that provides critical hardware and services for the International Space Station. Besides bolstering Russia's position in space, the Duma's vote appears to avert the nightmarish possibility that the space station might have to be de-manned for some indeterminate period, a scenario under consideration at NASA in 2002. The new budget, boosting the total annual Russian spending for the manned space flight program to 130 million dollars in 2003, will allow the Russian space contractor RKK Energia to complete critically needed supply ships and rescue vehicles for the long-duration crews of the station.
Keywords: International Space Station; RKK Energia; Russia; Russian space contractor; Funding; Long-duration crews; Manned space flight program; Manned space program; Rescue vehicles